2014
DOI: 10.1364/oe.22.017959
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the radiative recombination time in ZnO nanorods under an external magnetic field of 6T

Abstract: The Temperature dependence of the exciton radiative decay time in ZnO nanorods has been investigated, which is associated with the density of states for the intra-relaxation of thermally excited excitons. The photoluminescence decay time was calibrated by using the photoluminescence intensity in order to obtain the radiative decay time. In the absence of an external magnetic field, we have confirmed that the radiative decay time increased with temperature in a similar manner to that seen in bulk material (∼ T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…where τ PL (T) is the PL lifetime of the NTs at any given temperature and η th (T) is the ratio between the PL intensity at any given temperature and at 4 K. The validity of this method is based on the assumption that internal quantum efficiency is at its maximum at 4 K. 48 We observed that the radiative lifetime seems to increase in an approximately linear fashion as the temperature increases; that is, τ rad ∝ T, which is a signature of 1D-like confinement of carriers. 49,50 The three-dimensional (3D) behavior exhibited by bulk materials (represented by the dotted line in Figure 5d) diverges significantly from the experimentally observed dependence of the radiative lifetime on temperature. As the NT wall thickness (10−25 nm) is greater than the Bohr diameter (2a B ), 1D-like confinement can be ascribed to the quantum-confined Stark effect (QCSE) induced by both spontaneous and piezoelectric polarizations in wurtzite ZnO.…”
Section: ■ Introductionmentioning
confidence: 78%
“…where τ PL (T) is the PL lifetime of the NTs at any given temperature and η th (T) is the ratio between the PL intensity at any given temperature and at 4 K. The validity of this method is based on the assumption that internal quantum efficiency is at its maximum at 4 K. 48 We observed that the radiative lifetime seems to increase in an approximately linear fashion as the temperature increases; that is, τ rad ∝ T, which is a signature of 1D-like confinement of carriers. 49,50 The three-dimensional (3D) behavior exhibited by bulk materials (represented by the dotted line in Figure 5d) diverges significantly from the experimentally observed dependence of the radiative lifetime on temperature. As the NT wall thickness (10−25 nm) is greater than the Bohr diameter (2a B ), 1D-like confinement can be ascribed to the quantum-confined Stark effect (QCSE) induced by both spontaneous and piezoelectric polarizations in wurtzite ZnO.…”
Section: ■ Introductionmentioning
confidence: 78%
“…This results in a temperature dependence for the radiative recombination time ( τ r  ~  T α ). This experimental method has been used in bulk semiconductors ( β  = 0.5), quantum wells ( β  = 0), and quantum wires ( β  = −0.5), giving rise to α  = 1.5, 1, and 0.5, respectively212223. In this work, we have investigated β for a real QR in the absence of B in terms of τ r ( T ) and r(T ), which were obtained by using the temperature dependence of the linewidth, the time-resolved, and time-integrated photoluminescence (PL) intensities.…”
mentioning
confidence: 99%
“…A radiative process governs the lifetime of the InGaAs QW at temperatures below 100 K, whereas the contribution of nonradiative processes becomes significant as the temperature increase to greater than 100 K. This trend is consistent with the quenching process due to the thermal carrier escape estimated from the Arrhenius plot of the temperature dependence of PL intensity. From the power order of the temperature dependence ∼ T n of the radiative lifetime, due to the state densities, the dimensionality of a nanostructure can be estimated. From our estimation, we expected that n = 1 in the two-dimensional QW case and n = 0 (i.e., the lifetime is constant) in the zero-dimensional QD case. The observed radiative lifetime of the InGaAs QW was constant below 40 K and gradually increased above 40 K. The observed radiative lifetime increase was fitted by a power law and n was determined to be 1.02, using the data from 40 to 120 K, at which the radiative process is dominant.…”
Section: Resultsmentioning
confidence: 89%